Comparison of Solid and Solvent - Based Syntheses, Characterization and Antioxidant Property of Metal Complexes of Sodium Diclofenac (Fountain Journal of Natural and Applied Sciences, 2020)
Mechanosynthesis and solvent – based syntheses of transition metals (Ni, Co and Zn) complexes of Sodium diclofenac has been carried out by 1:1 molar ratio of the ligand to metal salts respectively. The synthesis of the metal complexes were confirmed by melting point determination, FT-IR (Fourier Transform Infra-red) and UV-visible spectroscopies. The ligand showed bidentate coordination to the metal ions through carboxylate moiety. Octahedral geometry was proposed for all the metal complexes. The antioxidant property of metal complexes was determined using DPPH (1,1-diphenyl-2-picrylhydrazyl) assay with Ascorbic acid as control. The antioxidant evaluation results revealed that the synthesized metal complexes are promising antioxidant agents.Keywords: Mechanosynthesis; DPPH; Carboxylate moiety; antioxidant evaluation